Bioinspired synthesis, characterization and antibacterial activity of plant-mediated silver nanoparticles using purple sweet potato root extract. (2nd July 2016) - Wang, L.; Xu, H.; Gu, L.; Han, T. T.; Wang, S.; Meng, F. B.
Abstract : Biosynthesis of silver nanoparticles (AgNPs) has become a promising synthetic strategy in nanotechnology in recent years. In this study, the purple sweet potato ( Ipomoea batatas L.) root extract was found to have a new application for the synthesis of AgNPs. It is a natural, eco-friendly and low-cost procedure that uses purple sweet potato extract as reducing and stabilizing agent. The as-prepared AgNPs were characterized by UV–visible spectroscopy, transmission electron microscopy, atomic force microscopy, X-ray diffraction and Fourier transform infrared spectroscopy. In addition, the biosynthesized AgNPs showed remarkable broad-spectrum antimicrobial activity against eight typical pathogens, including four clinic pathogens and four aquatic pathogens. Thus, the AgNPs synthesized with the help of purple sweet potato extract can be used as a powerful antibacterial agent and have great potential in different applications.